2018
DOI: 10.1016/j.bonr.2018.06.002
|View full text |Cite|
|
Sign up to set email alerts
|

Calcitriol and cancer therapy: A missed opportunity

Abstract: The vitamin D receptor is expressed in most tissues of the body – and the cancers that arise from those tissues. The vitamin D signaling pathway is active in those tissues and cancers. This is at least consistent with the hypothesis that perturbing this signaling may have a favorable effect on the genesis and growth of cancers. Epidemiologic data indicate that vitamin D signaling may be important in the initiation and outcome of a number of types of cancer. Many studies have shown that calcitriol (1,25 dihydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 157 publications
(184 reference statements)
0
37
0
Order By: Relevance
“…Herein, we show that, in addition to the effect per se , calcitriol also acted in a synergistic manner with the antifolate compound PEM, which, in association with cisplatin, is currently the standard first-line treatment for patients with advanced MPM ( 4 ). To the best of our knowledge, this is the first evidence on the effective combination of calcitriol and PEM in cancer cells, despite vitamin D derivatives previously showed the ability to potentiate in vitro and in vivo the antitumor effects of platinum analogs like carboplatin and cisplatin ( 5 , 9 , 45 ). Therefore, although not suitable as a single use against cancer, vitamin D derivatives might be considered as adjuvants in combination therapy with cytotoxic compounds, as already described for other types of cancers ( 9 , 11 ).…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Herein, we show that, in addition to the effect per se , calcitriol also acted in a synergistic manner with the antifolate compound PEM, which, in association with cisplatin, is currently the standard first-line treatment for patients with advanced MPM ( 4 ). To the best of our knowledge, this is the first evidence on the effective combination of calcitriol and PEM in cancer cells, despite vitamin D derivatives previously showed the ability to potentiate in vitro and in vivo the antitumor effects of platinum analogs like carboplatin and cisplatin ( 5 , 9 , 45 ). Therefore, although not suitable as a single use against cancer, vitamin D derivatives might be considered as adjuvants in combination therapy with cytotoxic compounds, as already described for other types of cancers ( 9 , 11 ).…”
Section: Discussionmentioning
confidence: 80%
“…The biological activity of calcitriol is mainly regulated by VDR, which modulates the expression of many target genes ( 5 , 28 ). Importantly, it has been shown that tumor progression may be correlated with lower VDR levels in different types of cancer ( 5 9 ), and a positive association between expression of VDR/calcitriol with improved prognosis was found in patients with lung adenocarcinoma ( 29 , 30 ). Furthermore, it has been recently demonstrated that vitamin D deficiency exacerbates pulmonary fibrosis in mice ( 31 ), whereas lung cancer cells expressing VDR are more responsive to the antiproliferative effect of calcitriol; in addition, high nuclear VDR expression has been associated with increased survival in lung cancer patients ( 29 , 30 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations